Gravity-driven water flow in networks theory and design - Ivanov, Azhaire (SCITUS Academics LLC, 2016)
"Gravity-driven water flow networks are a crucial method of delivering clean water to millions of people worldwide, and an essential agricultural tool. This book provides an all-encompassing guide to designing these water networks, combining theory and case studies. It includes design formulas for water flow in single or multiple, uniform or non-uniform diameter pipe networks; case studies on how systems are built, used, and maintained; comprehensive coverage of pipe materials, pressure ratings, and dimensions; and over 100 illustrations and tables. It is a key resource both for working engineers and engineering students and instructors"